Donating and Volunteering as Social Capital in Bogotá (2013)
While the term social capital has been in existence since 1835, it only became popular at the end of the twentieth century, with the emergence of the associational revolution and the appearance of the third sector. Since then, non-governmental organisations (NGOs), volunteering, philanthropic financing and solidarity organisations have all shaped a common discourse. From a social capital perspective, and on the basis of a social survey, this article investigates the determinants of solidarity and participation in NGOs in Bogotá, Colombia. We conclude that the expression of social capital in Bogotá is made manifest through donations and volunteering, factors which should be considered in fundraising activities. © 2012 Society for Latin American Studies.